Odpowiedzi

Najlepsza Odpowiedź!
2009-11-25T18:34:07+01:00
A)∫x+4y=11 |*(-2)
∫ 2x+5y=10
{-2x-8y=-22
{2x+5y=10
x sie skrócą, więc będzie
-8y+5y=-22+10
-3y=-12 |/(-3)
y=4
x=-5

b)3x+2y=5 |*(-1)
∫2x+2y=2
{-3x-2y=-5
{2x+2y=2
y sie skróca wiec bedzie
-3x+2x=-5+2
-x=-3 |/(-1)
x=3
y=-4
c)∫3x+2y=2
∫-3x+y=10
x sie skrócą wiec bedzie
3y=12
y=4
x=-2
2009-11-25T18:38:59+01:00
A)
x+4y=11|*-2
2x+5y=10

-2x-8y=-22
2x+5y=10

2x+5y-2x-8y=10-22
-3y=-12/:-3
y=4
2x+5*4=10
2x+20=10
2x=-10 |/2
x=-5
y=4

b)
3x+2y=5
2x+2y=2|*(-1)

3x+2y=5
-2x-2y=-2

3x+2y-2x-2y=5-2
x=3
2*3+2y=2
6+2y=2
2y=-4 |/2
y=-2
x=3

c)
3x+2y=2
-3x+y=10

3x+2y-3x+y=10+2
3y=12 |/3
y=4

-3x+4=10
-3x=6 |/(-3)
x=-2
2009-11-25T18:47:03+01:00
A) ∫x+4y=11
∫ 2x+5y=10
x=11-4y
2*(11-4y)=10
22-8y+5y=10
-8y+5y=10-22
3y=-12/:3
y=-4
x=11-4*(-4)
x=11-16
x=-5

b)∫3x+2y=5
∫2x+2y=2
2y=5-3x/:2
y=2,5-1,5x
2x+2(2,5-1,5x)=2
2x+5-3x=2
2x-3x=2-5
-x=-3/:-1
x=3
y=2.5-1.5*3
y=2.5-4.5
y=-2

c)∫3x+2y=2
∫-3x+y=10
y=10+3x
3x+2(10+3x)=2
3x+20+6x=2
9x=2-20
9x=-18/:9
x=-2
y=10+3*(-2)
y=10-6
y=4

to tyle:)Mam nadzieje że pomogłam:)